The art of home education: an investigation into the impact of context on arts teaching and learning in home education. Issue 6 (2nd November 2019) - Burke, Katie; Cleaver, David
ABSTRACT: This paper explores understandings and implications arising from research conducted into how home educating families approach learning in the creative arts. Through a series of online focus groups with 14 Australian home educating families, the authors sought to understand the strategies and learning activities that families employed when teaching their children about the arts, and the factors that influenced this process. An earlier paper based on this investigation uncovered the strategies employed by participating families, and in this successive paper, they now focus on the variety of ways that the arts learning strategies were flexibly incorporated into individual educational family practice according to the fluctuating needs and dynamics of individual contexts. The findings highlight how families engage in arts learning as a form of sociocultural practice, with individuals as joint members in a family 'Community of Practice' and where authentic, collaborative and child-centred arts experiences are valued.